In Vivo Evaluation of the Efficacy of a Nisin-Biogel as a New Approach for Canine Periodontal Disease Control - Eva Cunha; Luís Miguel Carreira; Telmo Nunes; Marta Videira; Luís Tavares; Ana Salomé Veiga; Manuela Oliveira (MDPI AG, 2022)
Periodontal disease (PD) is a common oral disease in dogs. Recent in vitro research revealed that nisin-biogel is a promising compound for canine PD control. In this work, a clinical trial was developed to assess the in vivo efficacy of nisin-biogel in dogs by determining the dental plaque index (DPI), gingivitis index (GI), and periodontal pocket depth (PPD) after dental administration. The biogel's influence on aerobic bacteria counts was also evaluated, as well as its acceptance/adverse effects in dogs. Twenty animals were allocated to one of two groups: a treatment group (TG) subjected to a dental topical application of nisin-biogel for 90 days and a control group (CG) with no treatment. Besides daily monitoring, on day 1 (T0) and at the end of the assay (T90), animals were subjected to blood analysis, periodontal evaluation, dental plaque sampling, scaling, and polishing. Statistical analysis with mixed models showed a significant reduction in mean PPD (estimate = −0.371, p-value < 0.001) and DPI (estimate = −0.146, p-value < 0.05) in the TG animals at T90. A reduction in the GI (estimate = −0.056, p-value > 0.05) was also observed but with no statistical significance. No influence on total bacterial counts was observed, and no adverse effects were detected. The nisin-biogel was revealed to be a promising compound for canine PD control.